Mediation of Spiritual Human Capital in the Relationship Between Transformational and Spiritual Leadership on the Performance of Prison Officers in West Kalimantan Province - makmur hidayah, huzaifah; Komari, Nurul; Daud, Ilzar (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Leadership in organizations is a process that involves many formal and informal leaders at all levels and in various organizational subunits. This study explores the influence of transformational leadership and spiritual leadership on spiritual human capital and officer performance at the West Kalimantan State Prison. Using a quantitative approach with the Structural Equation Modeling (SEM) method, this study tests the hypothesis that transformational and spiritual leadership influence spiritual human capital, which then mediates officer performance. The results of the analysis show that spiritual leadership has a significant influence on officer performance and spiritual human capital, while transformational leadership does not show a significant direct influence. Spiritual human capital was shown to mediate the relationship between spiritual leadership and officer performance. These findings emphasize the importance of meeting officers’ spiritual needs to enhance their performance, as well as the crucial role of spiritual leadership in organizations. This study provides insight into how effective leadership can enhance productivity and performance in the correctional context.